2021
DOI: 10.1186/s12885-021-08456-6
|View full text |Cite
|
Sign up to set email alerts
|

Elevated TYROBP expression predicts poor prognosis and high tumor immune infiltration in patients with low-grade glioma

Abstract: Background Tyrosine protein tyrosine kinase binding protein (TYROBP) binds non-covalently to activated receptors on the surface of various immune cells, and mediates signal transduction and cellular activation. It is dysregulated in various malignancies, although little is known regarding its role in low-grade glioma. The aim of this study is to explore the clinicopathological significance, prognostic value and immune signature of TYROBP expression in low-grade glioma (LGG). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 44 publications
(35 reference statements)
1
33
0
Order By: Relevance
“…In previous studies, the differential expression of MAD2L1 in many tumors was analyzed using the TIMER2.0 database [ 35 , 36 ]. It was found that the expression of the MAD2L1 gene was higher in BLCA, BRCA, CESC, CHOL, COAD, ESCA, GBM, HNSC, KIRC, LUAD, LUSC, PRAD, READ, STAD, and UCEC than in their corresponding paracancerous tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the differential expression of MAD2L1 in many tumors was analyzed using the TIMER2.0 database [ 35 , 36 ]. It was found that the expression of the MAD2L1 gene was higher in BLCA, BRCA, CESC, CHOL, COAD, ESCA, GBM, HNSC, KIRC, LUAD, LUSC, PRAD, READ, STAD, and UCEC than in their corresponding paracancerous tissues.…”
Section: Discussionmentioning
confidence: 99%
“…TYROBP is a transmembrane signaling polypeptide and triggers receptors on the immune cells’ surface [ 39 ]. TYROBP expression was significantly higher in the LGG tissues compared to the normal tissues and associated with worse prognosis and poor clinic pathological parameters in glioma [ 29 ]. VAMP8 is a SNARE protein, which function as an oncogene by promoting cell proliferation and therapeutic resistance in glioma [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the prognostic survival of PPP1R14A in various cancers revealed a strange phenomenon, which was inconsistent with the general understanding of the molecule ( Lu et al, 2021 ). For example, using Figures 4 – 6 , we can observe that among BLCA, COAD, and KIRP patients, the PPP1R14A high expression group showed a worse prognosis.…”
Section: Discussionmentioning
confidence: 76%